The dynamics of work environment and its impact on organizational objectives - Oluwatoyin Ojo Emmanuel (Goodwood Publishing, 2022)
Purpose: The purpose of this research is to analyze the importance of the internal work environment and how it can promote organizational productivity. A work environment in the organization must be taken seriously because it is a way of defining the organization itself, it embraces all physical features in the workplace that can promote effective work operation, the ability of workers to relate properly, interact effectively, and connect well with their colleagues or those in the top-level management on work-related issues. Research Methodology: This article adopts the secondary data through consultation of several textbooks, magazines, journals, and other publications. Findings: It was observed that the organization fails to promote a good internal working environment, poor working conditions, disordered workplace, fails to include the employee in decision-making processes which can affect the level of productivity and hinder organizational objectives. Limitations: The major limitations to the study are time constraints, access to literature, and the age of data since the research is based on secondary data. Contribution: The research can contribute immensely to the growth and development of any organization either public or private and every other government ministry on how to manage the internal work environment.